Estudi i edició crítica del proemi Aquest llibre s'intitula. - SOLÀ, MIQUEL SABATÉ (Scripta, 2023)
Càrcer was a copyist from the 17th century that wrote a proem in verse of great interest for the study of the transmission and the valoration of catalan poetry from the Barroque period. This article studies this introductory poem from two points of view. First of all, the article points out the importance of this poem in order to understand the relationship between three miscellaneous manuscripts that have survived into our present day. This gives us more elements for the consideration of the context for some of the poems included in these volumes, and it can also help us to establish the authorship of some of the poems that would otherwise remain unclear. On the other hand, this poem is also a singular artifact when it comes to the consideration of the authors of catalan barroque poetry by a contemporary author that is therefore removed from future judgement. All of this has been complemented with the edition of this poem, which had been unedited until now, by following textual criticism.